Clinical Ethicists Awakened: Addressing Two Generations of Clinical Ethics Issues Involving Undocumented Patients. Issue 4 (3rd April 2019) - Kuczewski, Mark
Abstract : Because the United States has failed to provide a pathway to citizenship for its long-term undocumented population, clinical ethicists have more than 20 years of addressing issues that arise in caring for this population. I illustrate that these challenges fall into two sets of issues. First-generation issues involve finding ethical ways to treat and discharge patients who are uninsured and ineligible for safety-net resources. More recently, ethicists have been invited to help address second-generation issues that involve facilitating the presentation for care of undocumented patients. In the current environment of widespread fear of deportation in the immigrant community, ethicists are working with health care providers to address patient concerns that prevent them from seeking care. I illustrate that in both generations of issues, values implicit within health care, namely, caring, efficiency, and promotion of public health, guide the strategies that are acceptable and recommended.